Informed Consent to Clinical Trial as Factor Determining Participation - Igor Mareev (Journal of Global Pharma Technology, 2018)
The informed consent (IC) form and the doctor involved in the research are the major sources of information for participants in clinical trial (CT). Thereby, they are directly influencing the perception of possible participants and they decisions about participation. However, significance of these factors for the participants in the BE study remains unclear. The leading method applied was a questionnaire survey: a volunteer (n=137), who has already experienced the practice of participation in clinical trial and satisfies the selection criteria, was once asked to fill in the questionnaire on his own. As the research progressed, all the respondents were divided into two groups: participants who got acknowledged about the IC by a doctor and independently. In the group of respondents, who read IC independently, students dominated. The significance of factors influencing the decision to participate in clinical trial was assessed on a five-point scale. Respondents noted the following as the most significant motivators: a cash reward, regular health observation and observation by professional experts. Negatively colored factors were the risk of side effects, adherence to restrictions, and the use of a new drug. Thus, research results showed that volunteers adequately assess the risks of participation in clinical trial. Material affluence plays a key role in motivation and determines the ‘professionalization’ of volunteers in the BE study. This factor is undoubtedly the leading risk of ethics violation.Keywords: Clinical trials, Bioequivalence, Informed consent, Perception, Motivation, Decision-making.